2013
DOI: 10.1007/s00330-013-3022-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of iterative reconstruction on CT coronary calcium quantification

Abstract: SAFIRE noise reduction techniques significantly affected the CAC, which potentially alters perceived cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 30 publications
6
43
2
1
Order By: Relevance
“…This finding is in agreement with recent studies, which show smaller variability for mass scores [26,38,41,42]. Many recent studies have shown that increasing levels of iterative reconstruction causes a reduction in CCS [12,16,40,[43][44][45][46][47][48]. This result was also established in our study.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This finding is in agreement with recent studies, which show smaller variability for mass scores [26,38,41,42]. Many recent studies have shown that increasing levels of iterative reconstruction causes a reduction in CCS [12,16,40,[43][44][45][46][47][48]. This result was also established in our study.…”
Section: Discussionsupporting
confidence: 83%
“…The effect of iterative reconstruction on quantitative measurements in cardiovascular imaging has been subject of recent studies [11][12][13][14][15][16][17][18]. One of the most commonly used cardiovascular risk assessment tools in CT is coronary calcium scoring (CCS).…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] An in vivo study by Kurata et al revealed that Agatston scores tend to decrease as sonogram affirmed iterative reconstruction (SAFIRE) levels increase. 18) Our observation that Agatston scores tend to decrease as IR levels increase further support these conclusions. The results of the present study, therefore, suggest that similar Agatston scores may be obtained when either standard-dose FBP or low-dose IR protocols are utilized.…”
Section: Discussionsupporting
confidence: 73%
“…Increasing levels of ASIR were associated with progressive decreases in Agatston and volume scores but not mass scores compared to FBP (60). Studies with IRIS and SAFIRE showed similar results: Agatston, volume, and mass scores were lower changing non-zero scores to zero in 4% of patients (61). Similarly, iDose 4 and IMR images each yielded 7% lower calcium score compared to FBP images with a risk reclassification rate of 2.4% (57).…”
Section: Coronary Stent Assessmentsupporting
confidence: 56%